An Immersed Raviart–Thomas Mixed Finite Element Method for Elliptic Interface Problems on Unfitted Meshes - Ji, Haifeng (Journal of scientific computing, 2022)
This paper presents a lowest-order immersed Raviart–Thomas mixed triangular finite element method for solving elliptic interface problems on unfitted meshes independent of the interface. In order to achieve the optimal convergence rates on unfitted meshes, an immersed finite element (IFE) is constructed by modifying the traditional Raviart–Thomas element. Some important properties are derived including the unisolvence of IFE basis functions, the optimal approximation capabilities of the IFE space and the corresponding commuting digram. Optimal finite element error estimates are proved rigorously with the constant independent of the interface location relative to the mesh. Some numerical examples are provided to validate the theoretical analysis.